Методические принципы построения обучающих систем; Физическое образование в вузах; Т. 9, № 1 - Ерофеева Г. В. Галина Васильевна; Крючков Ю. Ю. Юрий Юрьевич; Склярова Е. А. Елена Александровна; Малютин В. М. Василий Михайлович (2003, 2003)
Заглавие с экрана